Spatial analysis of imbalanced sex ratio at birth in China - Han, Xinping; W. N., W. Azman Saini; Law, Siong Hook; Rosland, Anitha; Wan Ismail, Wan Zulqurnain (SSRN - Elsevier, 2020)
Over the past many decades, China's sex ratio at birth (SRB) has risen significantly. This trend can have serious social and economic consequences as it may affect marriage market, labor market, economic activity and even the crime rate. Therefore, it is critically important for the Chinese government to explore the causes of this problem and address it accordingly. This study examines the causes of imbalance in China’s SRB using data from the Sixth National Population Census of China. The results reveal that the SRB in China has a positive spatial effect. Geographically, SRB is higher in eastern provinces and lower in western provinces. This suggests that the government should implement different policies in different provinces. Furthermore, the results of spatial econometric regression show that one child policy, sex selection technology, education and level of economic development significantly influence SRB. These findings imply that the government should promote fertility rates, educational opportunity, and economic development. Moreover, it should prevent sex-selective abortions.